2015
DOI: 10.7324/jabb.2015.3205
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of two catalytically distinct endoglucanases from Aspergillus nidulans

Abstract: This study reports purification and characterization of two catalytically distinct endoglucanases (EGI and EGII) from a thermotolerant fungus Aspergillus nidulans. The endoglucanases (EGI and EGII) exhibited molecular masses of 56 and 31 kDa and pIs of 3.6 and 3.8, respectively. EGI was putatively classified as GH7 family member catalyzed carboxymethyl cellulose, xyloglucan, barley β-glucan as well as pNP-β-D-lactopyranoside and pNP-cellobioside, and was optimally active at 50°C and pH 4.0. Whereas, EGII lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The value of k cat was between 5.6 and 11.5 min -1, and k cat /K M was between 42 to 400. Reports have also revealed that endoglucanases vary in their affinity towards polysaccharides as supported by the observed values of K M (Kaur, Oberoi, & Chadha, 2015). Glucose and [EMIM]OAc acted as uncompetitive inhibitors for β-glucosidase (BG), which in this context indicated the probability of IL binding to the E-S complex.…”
Section: Determination Of Kinetics Parameters Of Tr-cel With Cmc and mentioning
confidence: 87%
“…The value of k cat was between 5.6 and 11.5 min -1, and k cat /K M was between 42 to 400. Reports have also revealed that endoglucanases vary in their affinity towards polysaccharides as supported by the observed values of K M (Kaur, Oberoi, & Chadha, 2015). Glucose and [EMIM]OAc acted as uncompetitive inhibitors for β-glucosidase (BG), which in this context indicated the probability of IL binding to the E-S complex.…”
Section: Determination Of Kinetics Parameters Of Tr-cel With Cmc and mentioning
confidence: 87%